The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/1982-0216201410713
|View full text |Cite
|
Sign up to set email alerts
|

O distúrbio de linguagem em dois sujeitos com risco para o desenvolvimento em uma perspectiva enunciativa do funcionamento de linguagem

Abstract: Este estudo tem como objetivo analisar a importância de uma hipótese de funcionamento de linguagem, considerando as relações forma/sentido e os mecanismos e estratégias enunciativas na análise da linguagem de dois sujeitos com distúrbio de linguagem e risco ao desenvolvimento. Dois sujeitos e seus familiares foram acompanhados do primeiro ao décimo oitavo mês de idade, por meio dos Índices de Risco ao Desenvolvimento Infantil. Entre 21 e 24 meses, foram filmados com familiares (mãe, pai, irmão) e com a pesquis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
10

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 17 publications
0
6
0
10
Order By: Relevance
“…The preparation of the instrument initially took into account the enunciative mechanisms and strategies proposed by Silva (24) and the clinical experience of the authors in the follow-up of risk infants who developed a risk for language acquisition (21)(22)(23)25) . After formulated, the items were submitted to expert judges to judge on their clarity and relevance.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The preparation of the instrument initially took into account the enunciative mechanisms and strategies proposed by Silva (24) and the clinical experience of the authors in the follow-up of risk infants who developed a risk for language acquisition (21)(22)(23)25) . After formulated, the items were submitted to expert judges to judge on their clarity and relevance.…”
Section: Methodsmentioning
confidence: 99%
“…In the national literature, some studies have addressed the standardization of tests such as Denver II (15,16) , and other instruments created in Brazil (17)(18)(19)(20) . There are also studies that reflect on the effects of psychic risk in the language of babies (21)(22)(23) . Few studies use declarative references in the qualitative analysis of language (22,23) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the study suggests that gestational age, low weight at birth and gender may be more influential in the long term in these children, thus being necessary to monitor this population -as has been observed in other studies reviewed (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) . These results evidenced the importance of monitoring these children from birth, although none of them followed-up on psychological factors such as those proposed by Kupfer et al (39) , indicated as closely related to language acquisition (40) . Among the psychosocial factors that may affect child development, maternal mood states were analyzed in a study with Clinical Risk Indicators for Child Development (CRICHD) (41) .…”
Section: Discussionmentioning
confidence: 78%
“…Vários estudos têm comprovado a relevância dos IRDIs na detecção de risco ao desenvolvimento psíquico e sua correlação com alterações no exercício das funções parentais (Kupfer & Bernardino, 2009;Beltrami et al, 2013), dificuldades alimentares, psicomotoras e de linguagem do bebê (Vendrúscolo et al, 2012;Flores & Souza, 2014;Oliveira & Souza, 2014;Vendrúscolo, 2014). O estudo de Ouss (2013) realiza uma primeira análise dos sinais PREAUT em sujeitos com síndrome de West observando que esses sinais possuem sensibilidade e especificidade para a detecção precoce do autismo.…”
Section: Introductionunclassified